The Improved X-ray Detector (iXRD) on Sharjah-Sat-1, design principles, tests and ground calibration - Kalemci, Emrah; Ali M. Altıngün; Bozkurt, Ayhan; A. R. Aslan; Yalçın, Refik; Gökalp, Kaya; Veziroğlu, Kaan; Fernini, Ilias; A. Manousakis; Yaşar, Ali; Diba, Milad; Karabulut, Boğaç; et al. (Research Square Platform LLC, 2022)
Abstract The ixRD is the primary science payload on Sharjah-Sat-1, a 3U CubeSat expected to be launched in Q4, 2022. Its main scientific goal is monitoring bright hard X-ray sources and transients in 20 - 200 keV band. The iXRD consists of a CdZnTe crystal (6.45 cm2 area, 5 mm thickness), a Tungsten collimator with square holes with an opening angle of 4.26o, readout and control electronics and power circuitry, a back-shield and mechanical structures. Some of the design elements of iXRD have been inherited from the XRD on BeEagleSat with significant improvements in terms of collecting area, X-ray background and electronic noise. In this article, the design of the iXRD is discussed in detail taking into account mechanical, electronics, control software and data handling aspects. Its expected performance is determined after ground calibration. Depending on the pixel size, the energy resolution is 4 - 7 keV at 60 keV and the minimum detectable energy is 19 - 23 keV.
Keywords: X-ray detector; Astronomy; Biomedical Engineering; Dual-Energy Computed Tomography; FOS: Medical engineering; Quantum mechanics; Engineering; Collimator; Infrared Detector Technologies; FOS: Electrical engineering, electronic engineering, information engineering; Neutron Imaging and Analysis Techniques; Optoelectronics; Electrical and Electronic Engineering; Computer network; Radiation; Network packet; Physics; CubeSat; Detector; Optics; Infrared Detectors; Computer science; Payload (computing); Scintillation Detector Technology; Physics and Astronomy; Satellite; Electrical engineering; Physical Sciences; Calibration; Electronics